2019
DOI: 10.21082/blpn.v25n2.2019.p1-14
|View full text |Cite
|
Sign up to set email alerts
|

Study on Diversity and Potency of Some Macro Mushroom at Gunung Gede Pangrango National Park

Abstract: <p>Biodiversity is a valuable asset which should be preserved and protected. Gunung Gede Pangrango National Park (GGPNP) is one of the conservation areas with a high level of biodiversity in Indonesia. Currently, mushroom diversity in GGPNP is rarely reported. Inventory of mushroom diversity is the first step of actions to maintaining germplasm and maximizing its potential usage<br />in the future. In this paper, we explain how to use macroscopic characters to help identification of macro mushroom.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
14
0
7
Order By: Relevance
“…Lentinus is reported as a culinary-medicinal mushroom that possesses nutritious substances and biological activities (Lee et al, 2013;Mohammadnejad et al, 2019). Both Lentinus found in this study were different in colour and size with (Putra et al, 2019b;Putra, 2020a).…”
Section: Lentinus Sp1mentioning
confidence: 65%
See 2 more Smart Citations
“…Lentinus is reported as a culinary-medicinal mushroom that possesses nutritious substances and biological activities (Lee et al, 2013;Mohammadnejad et al, 2019). Both Lentinus found in this study were different in colour and size with (Putra et al, 2019b;Putra, 2020a).…”
Section: Lentinus Sp1mentioning
confidence: 65%
“…Members of the Agaricales are distributed worldwide with many representatives in tropical and temperate regions and a few species in arctic-alpine areas and deserts (Vellinga, 2004). In Indonesia, Putra et al, (2017;2018;2019a;2019b) and Putra (2020a) reported that Agaricales always found both in the natural and tourism areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 13 wild mushrooms namely :Amanita sp.1, Armillaria sp.1, Armillaria sp.2, Auricularia sp., Clitocybe sp., Crepidotus sp., Fomitopsis sp., Ganoderma sp., Lepiota sp.1, Microporus sp., Panaeolus sp., Polyporus sp., and Rigidoporus sp.,were collected from Mekarsari Tourism Park, Indonesia in July 2017 and Gede Pangrango Mountain National Park, Indonesia in July-August 2018 as described by Putra et al (2018;2019). Epigeal parts of the mushrooms were cleaned, dried, and then grounded by blender into small pieces.…”
Section: Wild Mushroom Extract Preparationmentioning
confidence: 99%
“…Jamur merupakan organisme heterotrof yang bisa ditemukan di berbagai relung ekologi karena gaya hidupnya yang kosmopolitan (Putra et al, 2017) (Putra, Sitompul, and Chalisya 2018) (Putra et al, 2018) (Putra, Nasrullah, and Dinindaputri 2019) (Putra, 2020a) (Putra, Amelya, Nugraha, et al 2020) (Putra, 2020c) . Hingga saat ini telah diketahui sebanyak 70.000 -140.000 jamur yang telah didokumentasikan (Hawksworth 2001) (Blackwell 2011) dari total estimasi 1.500.000 jamur yang berada di alam (Blackwell 2011).…”
Section: A Latar Belakangunclassified